THE ASSESSMENT PROCEDURE MAKING AUTOMATIC DIGITAL ELEVATION MODEL (DEM) USING PLEIADES SATELLITE IMAGERY (CASE STUDY: BANDUNG- WEST JAVA) - IKA ARYANI (NIM: 25114008), DIAN
The enforcement of base geospatial information in Indonesia is the responsibility of Geospatial Information Agency (BIG). This is in accordance with Law Number 4 of 2011 on Geospatial Information. The acceleration of national development urges BIG to provide topographic maps in various scales in a short time. The topographic maps can be derived from Digital Elevation Model (DEM), which can be obtained from satellite imagery data extraction. This result might be achieved by using a Very High Resolution Satellites (VHRS) Imagery, such as Pleiades Satellite. The main objective of this research is to review the procedures of Automatic DEM Extraction in order to obtain minimum error. The systematic implementations of this research are modeling the sensor, generating automatic tie point and performing automatic DEM extraction. The sensor modeling used Rational Function Model (RFM) and Rational Polynomial Camera (RPC) model parameters. Ground Control Points (GCPs) and Independent Control Points (ICPs) were used for the RFM refinement. Automatic tie point generation is done by matching the same object between pairing combination of tristereo Pleiades satellite imagery. Furthermore, the automatic DEM extraction process can be executed. The results of DEM extraction can be either point cloud data or mesh data which are verified by comparing the models. This is lead to acquire pairing combination of Pleiades imagery data which has the smallest error value among all of them. The comparison showed that the tri stereo pairing combination of the DEM extraction model has a lower accuracy than the backward – nadir pairing combination. However, the use of tri stereo image pairing combination is still better than the forward – nadir pairing combination.